Effects of Cranberry Extract (Vaccinium macrocarpon) Supplementation on Lipid Peroxidation and Inflammation in Patients with Chronic Kidney Disease (Stages 3-4): A Randomized Controlled Trial - Laís de Souza Gouveia Moreira; Karla Thaís Resende Teixeira; Ludmila F. M. F. Cardozo; Livia Alvarenga; Bruna Regis; Jessyca Sousa de Brito; Viviane de Oliveira Leal; Natalia Alvarenga Borges; Isabela de Souza da Costa Brum; José Carlos Carraro-Eduardo; Giovanna B. Borini; Andresa A. Berretta; et al. (Journal of Nutrition and Metabolism)
Background. Growing evidence suggests that bioactive compounds in berry fruits may mitigate inflammation in patients with chronic kidney disease (CKD). Objectives. To evaluate cranberry (Vaccinium macrocarpon) supplementation effects on modulation of transcription factors involved in inflammation and oxidative stress in nondialysis (stages 3 and 4) patients with CKD. Design/Participants. A randomized, double-blind, placebo-controlled study was performed with 30 patients to receive capsules containing cranberry extract (1000 mg/day) or placebo (1000 mg/day of corn starch) for two months. Measurements. The mRNA expression of nuclear factor-erythroid 2-related factor-2 (Nrf2) and nuclear factor-kB (NF-kB) was evaluated in peripheral blood mononuclear cells (PBMCs) by quantitative real-time polymerase chain reaction. Thiobarbituric acid reactive substances (TBARS) were measured in the plasma to assess oxidative stress. Interleukin-6 (IL-6) plasma levels were assessed by enzyme-linked immunosorbent assay and C-reactive protein (CRP) by immunoturbidimetric method. Results. Twenty-five patients completed the study: 12 in the cranberry group (56.7 ± 7.5 years and body mass index (BMI) of 29.6 ± 5.5 kg/m2) and 13 in the placebo group (58.8 ± 5.1 years and BMI 29.8 ± 5.4 kg/m2). There were no differences in NF-kB or Nrf2 mRNA expressions (p=0.99 and p=0.89) or TBARS, CRP, and IL-6 plasma levels after cranberry supplementation. Conclusions. The cranberry extract administration (1000 mg/day) did not affect Nrf2 and NF-kB mRNA expression, oxidative stress, or inflammatory markers levels in nondialysis CKD patients. This trial is registered with NCT04377919.